Food Fiction and Food Fact in Homer’s Iliad - Minchin, Elizabeth (Petits Propos Culinaires, 2024)
A catalogue of the foodstuffs and culinary practices mentioned in the course of the Homeric poems would be tedious and misleading, if we were not to try to establish the literary and social contexts in which the poet has established these items. We shall observe in the story of the Iliad the role that food and its rituals play in the establishment and maintenance of social relationships between its characters. We shall observe how, in the telling of the story, the poet has drawn on images of food and its preparation, a source of general and abiding interest, to establish a ready bond between himself and his audience, between his audience and his song.